A Platform for Working Class Unity? The Revolutionary Communist Party's The Red Front and the pre-history of Living Marxism/Spiked Online in the 1980s. Issue 1 (2nd January 2023) - Smith, Evan
ABSTRACT: In recent years, one of the most controversial stories on the British left is the trajectory of the far left Trotskyist group, the Revolutionary Communist Party (RCP) to the libertarian/contrarian online publication Spiked!, via the magazine Living Marxism . The evolution of the RCP into Spiked! has been explored somewhat by journalists, but it has yet to be explored in depth by historians. This paper argues that in the history of the RCP, The Red Front is an often overlooked turning point for the party towards rejection of conventional left thinking in the 1990s and eventual rejection of Marxist politics.